Effect of Intradiscal Methylene Blue Injection in Endoscopic Transforaminal Lumbar Discectomy - Sankarnath Pirabakaran; Babu Aloy; Manikandan Pavanasam (Journal of Orthopedics and Joint Surgery)
Background: Low back pain reduces the quality of life. The most common cause is lumbar disc prolapse. Endoscopic discectomy is a minimally invasive procedure used to treat lumbar disc prolapse. The use of intradiscal methylene blue injection in endoscopic lumbar discectomy improves patient's functional outcomes. Aim and objective: To evaluate the functional outcome of methylene blue injection in the endoscopic transforaminal lumbar discectomy in lumbar disc disease patients and clinical improvement in the form of postoperative (postop) radicular pain relief, early return to daily activities, and occupation. Materials and methods: A mixture of 1 mL 1% methylene blue and 1 mL 2% lidocaine. A 30° spinal endoscope with a working channel of 4.1 mm was used in this study. Study design prospective cohort study. A total of 20 patients with lumbar disc prolapse operated with transforaminal endoscopic lumbar discectomy with methylene blue injection. According to pain improvement, functioning abilities, and clinical symptoms, results were done based on the modified Oswestry disability index. Results: In our study, 90% of patients have postop radicular pain relief within 1 week. Around 85% of patients returned to their normal daily day-to-day activities within 3 weeks. Around 80% of patients returned to their work within 4 weeks. Around 75% of patients had neurological recovery in between 3 and 5 weeks. The modified Oswestry disability index in preop and postop patients were studied. The mean value significantly decreased from 69.5% in preop to 31.5% in postop conditions. The p-value is 0.00 (p-value < 0.05) and significant. In Macnab's criteria, our study shows an excellent to good outcome of 75%. Conclusion: This study showed that the use of intradiscal methylene blue injection in endoscopic transforaminal lumbar discectomy gives good radicular pain relief. It improves the accuracy and efficacy of endoscopic spine surgery.